Mapping Waqf Research: A 15-Year Bibliometric Study of Malaysia and Indonesia - Hanim Hj Misbah; Fuadah Johari (Center for Islamic Economics and Development Studies (CIEDS)- P3EI, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
Non-Indexed Publication